The condition factor of fishes from two river basins in São Paulo state, Southeast of Brazil - Gomiero, Leandro Muller [UNESP] (2005)
This work describes the relative condition factor of the Hypostomus strigaticeps, Astyanax altiparanae, Astyanax scabripinnis, Astyanax fasciatus, Astyanax sp1., Characidium aff. zebra, Piabina argentea, Hypostomus ancistroides, Hypostomus sp1., Parodon tortuosus, Serrapinus heterodon, and Bryconamericus sp., of the APA of São Pedro and Analândia (22°-23°S and 47°30'-48°30'W). The condition factor provides information about the physical state of the animal in the environment. In order to compare different species, the relative condition factor was used. Variations in this factor were correlated with variations through the year and with subsequent alterations in the physiological state of the fishes. The relative condition factor was shown to be efficient in indicating changes in fish condition throughout the year.